Enhancing EFL Learners’ Speaking Skills through AI-Assisted Interventions: A Statistical Evaluation - Hotamova Iroda Ibrohimovna (Genius Journals, 2025)
This study investigates the effectiveness of artificial intelligence (AI) technologies in enhancing English as a Foreign Language (EFL) learners’ speaking competence through systematic instructional tasks. A structured trend analysis over six weeks was conducted to examine learners’ progression in overall speaking performance and specific skills including grammar, pronunciation, and communication. Repeated measures analysis of variance and inferential statistics demonstrated significant improvements in learners’ performance. The findings indicate that AI-supported interactive tasks can effectively enhance multiple dimensions of speaking competence in higher education. The study concludes that AI integration contributes to more personalized and efficient language learning environments
Keywords: artificial intelligence; EFL speaking competence; trend analysis